CDIEA: Chaos and DNA Based Image Encryption Algorithm - Arı, Ali (Fırat Üniversitesi, 2023)
A proposal for an image encryption algorithm called Chaos and DNA Based Image Encryption Algorithm (CDIEA) has been put forward. CDIEA is a combination of block cipher algorithms, permutations, chaotic keys, and DNA operations. It leverages the strong structures of modern cryptography and the properties of chaotic systems, rather than relying solely on chaos. The permutations used in CDIEA are constructed using a strategy called the wide trail design, which makes it resilient to many forms of cryptanalysis. CDIEA operates as a byte-oriented SP-network and has been confirmed to have high security for practical image encryption through both theoretical analysis and computer experiments.

Kaos ve DNA Tabanlı Görüntü Şifreleme Algoritması (CDIEA) adı verilen bir görüntü şifreleme algoritması önerisi ortaya atılmıştır. CDIEA, blok şifreleme algoritmaları, permütasyonlar, kaotik anahtarlar ve DNA işlemlerinin bir kombinasyonudur. Yalnızca kaosa güvenmek yerine, modern kriptografinin güçlü yapılarından ve kaotik sistemlerin özelliklerinden yararlanır. CDIEA'da kullanılan permütasyonlar, onu birçok kriptanalize dayanıklı hale getiren geniş iz tasarımı adı verilen bir strateji kullanılarak oluşturulmuştur. CDIEA, bayt yönelimli bir SP ağı olarak çalışır ve hem teorik analiz hem de bilgisayar deneyleri yoluyla pratik görüntü şifreleme için yüksek güvenliğe sahip olduğu onaylanmıştır.
CDIEA: Kaos ve DNA Tabanlı Görüntü Şifreleme Algoritması
Keywords: Engineering; Mühendislik